Characterization of Primary Cilia in Osteoblasts Isolated From Patients With ADPKD and CKD. (23rd February 2021) - Pereira, Renata C; Gitomer, Berenice Y; Chonchol, Michel; Harris, Peter C; Noche, Kathleen J; Salusky, Isidro B; Albrecht, Lauren V
ABSTRACT: Autosomal dominant polycystic kidney disease (ADPKD) is the most common inherited cause of chronic kidney disease (CKD) and leads to a specific type of bone disease. The primary cilium is a major cellular organelle implicated in the pathophysiology of ADPKD caused by mutations in polycystin‐1 ( PKD1 ) and polycystin‐2 ( PKD2 ). In this study, for the first time, cilia were characterized in primary preosteoblasts isolated from patients with ADPKD. All patients with ADPKD had low bone turnover and primary osteoblasts were also obtained from patients with non‐ADPKD CKD with low bone turnover. Image‐based immunofluorescence assays analyzed cilia using standard markers, pericentrin, and acetylated‐α‐tubulin, where cilia induction and elongation were chosen as relevant endpoints for these initial investigations. Osteoblastic activity was examined by measuring alkaline phosphatase levels and mineralized matrix deposition rates. It was found that primary cilia can be visualized in patient‐derived osteoblasts and respond to elongation treatments. Compared with control cells, ADPKD osteoblasts displayed abnormal cilia elongation that was significantly more responsive in cells with PKD2 nontruncating mutations and PKD1 mutations. In contrast, non‐ADPKD CKD osteoblasts were unresponsive and had shorter cilia. Finally, ADPKD osteoblasts showed increased rates of mineralized matrix deposition compared with non‐ADPKD CKD. This work represents the first study of cilia in primary human‐derived osteoblasts from patients with CKD and patients with ADPKD who have normal kidney function, offering new insights as bone disease phenotypes are not well recapitulated in animal models. These data support a model whereby altered cilia occurs in PKD‐ mutated osteoblasts, and that ADPKD‐related defects in bone cell activity and mineralization are distinct from adynamic bone disease from patients with non‐ADPKD CKD. © 2021 The Authors. JBMR Plus published by Wiley Periodicals LLC. on behalf of American Society for Bone and Mineral Research.